1997
DOI: 10.1098/rstb.1997.0060
|View full text |Cite
|
Sign up to set email alerts
|

Can repeated plasma donation by asymptomatic HIV–infected individuals delay the onset of AIDS?

Abstract: SUMMARYHealthy HIV-positive regular donors of plasma in a programme of passive immunotherapy for AIDS patients were studied over a period of about two years. None developed symptoms of clinical progression ; most seemed to make substantial gains of CD4 cells by comparison with asymptomatic individuals who were not donating. The effects of donation did not seem to diminish with repetition, and donor CD4 counts tended towards stabilizing within normal limits. Asymptomatic HIV-positive individuals were compared i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

1998
1998
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Hyperactivation of the immune system is a marker of HIV-1 progression to AIDS, and immunosuppressive therapy has indeed been shown to be of benefit in some cases in conjunction with antiretroviral therapy (Argyropoulos & Mouzaki, 2006). Plasmapheresis or immunoadsorption have also been used in AIDS therapy and have shown significant benefit both in the symptoms associated with AIDS (peripheral polyneuropathy and neuromuscular disorders (Cornblath, 1988;Kiprov et al, 1988;Salim et al, 1989) or vasculitis (Cohen et al, 1993), and in the progression of AIDS itself (Raven, 1994;Bainbridge et al, 1997), including a rise in the CD4 + T-cell count (Tomar et al, 1984;Blick et al, 1998). These plasma exchange techniques remove all antibodies, some of which may well be beneficial, as well as other protein messengers including beneficial or deleterious cytokines, growth factors or peptide messengers.…”
Section: Discussionmentioning
confidence: 99%
“…Hyperactivation of the immune system is a marker of HIV-1 progression to AIDS, and immunosuppressive therapy has indeed been shown to be of benefit in some cases in conjunction with antiretroviral therapy (Argyropoulos & Mouzaki, 2006). Plasmapheresis or immunoadsorption have also been used in AIDS therapy and have shown significant benefit both in the symptoms associated with AIDS (peripheral polyneuropathy and neuromuscular disorders (Cornblath, 1988;Kiprov et al, 1988;Salim et al, 1989) or vasculitis (Cohen et al, 1993), and in the progression of AIDS itself (Raven, 1994;Bainbridge et al, 1997), including a rise in the CD4 + T-cell count (Tomar et al, 1984;Blick et al, 1998). These plasma exchange techniques remove all antibodies, some of which may well be beneficial, as well as other protein messengers including beneficial or deleterious cytokines, growth factors or peptide messengers.…”
Section: Discussionmentioning
confidence: 99%
“…A significant question is therefore the effect of repeated plasma donation on the progress of their own disease. A study over a two-year period of 26 HIV-1 positive healthy plasma donors monitored substantial increases in their levels of circulating CD4+ T-helper cells, as compared to a similar group of healthy asymptomatic HIV-infected individuals who were submitting routine blood specimens through the same clinic, but were not donating (Bainbridge et al, 1997). Most donors seemed to be moving towards stabilising their CD4+ helper T-lymphocyte levels rather than losing cells.…”
Section: (12 ) Therapeutic Plasmapheresismentioning
confidence: 99%
“…Healthy HIV‐positive plasma donors were studied over 2 years. Their CD4 cell count made substantial gains and tended toward stabilizing to normal . In another study, healthy plasma donors showed an increase of serum testosterone levels (Kiprov, Ivanova, personal communication).…”
mentioning
confidence: 95%